Covid-19: Effect of lockdown on mental and physical health. - Gautam, Dikshya (2020)
EXECUTIVE SUMMARY: Background Long lockdown caused by COVID-19 has created the negative impact in mental and physical health of the general population. Being at the home all the time for such a long period has increased the vulnerability to mental health problems as well as physical health such as increased stress and anxiety, insomnia, over-eating, lack in physical activities. The people are dealing with economic problem and also the financial insecurities as many of them have lost their jobs and are job-less; this definitely creates frustration among people. Along with that intake of information in excessive amount either that‟s real or fake information, is also the problem created by lockdown. The amount of screen time has also increased up to great extent. In this kind of situation there is threat among people to give up their life, go on depression and also do suicide. Aim The aim is to study the effect of Lockdown on Mental and Physical health due to COVID-19 among general population in Madhyapur Municipality, Bhaktapur, Nepal. Materials and Methods The study was cross-sectional study. It is a quantitative study where population above 18 years were study population. The questionnaire was filled through face to face interview. Pre-testing of the tools was done prior to data collection. Findings There was significant change seen in dietary pattern due to lockdown. 62.3% participants believe that lockdown caused change in dietary pattern. Also, there was change in number of meals or snacks consumed during lockdown than earlier. 63.8% claimed to have change in number of their lunch or snacks. Most of the participants preferred going to the local market rather than supermarket i.e. 54% during the period of lockdown for necessary foods and stuffs. Almost half of the participants used to exercise during the lockdown period i.e. 49.4%, although there seems to be little declination than before lockdown. But the timing of exercise had increased during lockdown than before lockdown period. And among those who exercised during lockdown, 94.2% believed that exercise did help them to deal with lockdown somehow. Moving towards social media, among all participants 82.70% participants were actively using SM during lockdown period. The hours of usage of SM had drastically increased during the lockdown period according to this study. Those who used to use SM to communicate, most of them thought it was a good option during time of COVID-19, but 35.3% said they would prefer the communication directly rather than through SM. Also almost 20.60% participants said SM increased their level of stress through overflow of information. The anxiety was seen highly among participants. Sun threshold anxiety was 27.9%, moderate anxiety was 45.2% and severe anxiety was seen 24.8%. Though anxiety was high insomnia has been seen lower comparatively. 15.5% had sub threshold insomnia while 3.4% had moderate insomnia during lockdown. Conclusion The effect of lockdown has been clearly seen from the results/ findings. From change in dietary pattern, to number of meals/snacks in a day has been noted. The increase in timing of exercise has been seen during lockdown. Drastic uses of SM have been noted during the time of study. Likewise, the anxiety level was seen really high due to COVID-19. Significant amount of insomnia was also seen. This shows that lockdown had shown its effect on both mental and physical health. Key words: COVID-19 AND Mental Health, COVID-19 AND Mental Health AND Quarantine, COVID-19 AND Mental Health AND Lockdown, COVID-19 AND Mental Health AND Exercise, COVID-19 AND Mental Health AND Eating, COVID-19 AND Mental Health AND Eating